Digital Financial Inclusion and Its Impact on Icroenterprise Productivity in Indonesia - Anjasmara Pratama Hadi; Rosita Mei Damayanti; Yingqin Zheng (Economics Note, 2026)
Digital financial inclusion has become a critical driver of microenterprise development in emerging economies. In Indonesia, the rapid diffusion of fintech platforms, mobile banking, and digital payment systems has transformed how microenterprises access financial services. This study examines the impact of digital financial inclusion on microenterprise productivity in Indonesia. The research adopts a quantitative explanatory design using secondary data from national surveys and empirical findings from prior peer-reviewed studies. Data were analyzed through comparative synthesis and thematic integration of productivity indicators, including revenue growth, operational efficiency, and financial management capability. The results indicate that digital financial inclusion significantly enhances microenterprise productivity by improving access to capital, reducing transaction costs, and strengthening financial literacy. Fintech adoption and digital financial literacy emerge as key mediating factors. However, the study also identifies structural constraints, including uneven digital infrastructure, regulatory complexity, and low digital readiness among informal microenterprises. The findings reinforce financial intermediation theory and the technology acceptance model within the context of developing economies. This study contributes to the literature by providing an integrated empirical perspective on digital financial inclusion and microenterprise productivity in Indonesia. Policy implications highlight the need for inclusive digital finance regulation, targeted literacy programs, and infrastructure development to sustain microenterprise growth.